HUBUNGAN LAMA MENDERITA DIABETES MELITUS DAN KADAR GULA DARAH DENGAN KUALITAS TIDUR PADA PASIEN DIABETES MELITUS TIPE 2 - Rina Kriswiastiny; Siti Marini Yunita; Nopi Sani; Tony Prasetia (CV. Jasa Sukses Abadi, 2023)
Abstract Diabetes mellitus or what is known in laymen as diabetes is one of the four priority non-communicable diseases which are the target of follow-up by world leaders. The number of cases and prevalence of diabetes has continued to increase over the last 10 years. Diabetes mellitus (DM) is a chronic disease characterized by blood glucose levels above normal values (> 200 mg/dl). This study aims to determine whether there is a relationship between duration of diabetes mellitus and blood sugar levels with sleep quality in type 2 diabetes mellitus patients. This study used an observational analytic method with a cross sectional approach. It was found that there was no relationship between duration of suffering from type 2 diabetes mellitus and sleep quality with the result Asym-sig = 0.585 (p >0.05). It is known that there is no relationship between blood sugar levels and sleep quality with the result Asym-sig = 0.887 (p>0.05). There is no significant relationship between duration of suffering from type 2 diabetes mellitus and blood sugar levels with sleep quality.